USOPC cuts staff as coronavirus forces savings (Reuters, 2020)
The United States Olympic and Paralympic Committee (USOPC) is eliminating 51 jobs and furloughing 33 employees in a bid to reduce expenses by 10-20% over the next four years as it faces tough financial times due to the novel coronavirus outbreak.